2018
DOI: 10.3233/ves-170625
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and serum 25-hydroxyvitamin D in patients with idiopathic benign paroxysmal positional vertigo

Abstract: Abstract. The aim of this study was to evaluate the relationship between bone mineral density (BMD) and 25-hydroxyvitamin D with the occurrence and recurrence of BPPV. The records of 130 idiopathic BPPV patients (55 ± 12 years old, 30 men and 100 women) and 130 age-and sex-matched controls who underwent bone mineral densitometry between April 2012 and September 2015 were reviewed retrospectively. We compared the BMD and serum 25-hydroxyvitamin D between the patients and controls, and also compared the BMD betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…Only age is an independent predictor of recurrence, although a low BMD and age correlate with the recurrence of BPPV. 25 Similar findings regarding gender and age were observed in our study, since there was a statistically significant difference in the amount of vitamin D, age, and gender in the BPPV group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only age is an independent predictor of recurrence, although a low BMD and age correlate with the recurrence of BPPV. 25 Similar findings regarding gender and age were observed in our study, since there was a statistically significant difference in the amount of vitamin D, age, and gender in the BPPV group.…”
Section: Discussionsupporting
confidence: 89%
“…The 25-OH-vitamin D dosages were performed in serum samples by fully automated chemiluminescent method (Architect iSR2000-Abbott). They were adopted according to 25 20,21 The BMD was evaluated with the QDR 4500 duo-energy densitometer (Hologic Inc., Bedford, MA, USA) in the lumbar spine (L1-L4), femoral neck and total femur regions. For the analysis, we used the criteria of the World Health Organization, 22 normal BMD with T-score up to À1.0 AE standard deviation (SD), osteopenia with T-score between À1.0 to À2.4 AE SD, and osteoporosis with T-score À2.5 AE SD at any bone site.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“… 32 , 41 A large population-based study including 6,649 patients with osteoporosis and 26,596 matched controls demonstrated that the risk of manifesting BPPV in patients with osteoporosis was a 1.82-fold higher than in the controls. 42 A usual cause of disorders in the metabolism of calcium is the deficiency of vitamin D. Yang et al 43 evaluated the relationship between bone mineral density and 25-hydroxyvitamin D with the presence and recurrence of BPPV. The authors found that low bone mineral density in women and low serum 25-hydroxyvitamin D levels in men were significantly associated with the recurrence of BPPV, whereas age was an independent predictor of recurrence.…”
Section: Etiologymentioning
confidence: 99%
“…reported that serum 25(OH) D levels were lower in 37 male patients with BPPV than in controls. While, a retrospective study including 30 male patients with BPPV revealed that serum 25(OH) D concentrations were significantly decreased compared with controls, whereas BMD results showed no significant differences ( 12 ). Different from previous findings, there were no significant differences in mean T-scores and vitamin D levels, osteoporosis, and vitamin D deficiency prevalence between 29 male BPPV patients and controls ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high incidence of BPPV in women, most previous studies selected women as study subjects. Thus, there are few reports assessing BMD and serum levels of 25-hydroxyvitamin D(25(OH) D) in male idiopathic BPPV patients, and the conclusions of these papers are contradictory( 7 , 9 , 12 , 19 , 20 ). Moreover, none of these studies examined biochemical bone turnover markers (BTM) in male idiopathic BPPV patients.…”
Section: Introductionmentioning
confidence: 99%